Purpureocillium lilacinum and metarhizium anisopliae isolates for biocontrol against lesion and root-knot nematodes infecting sugarcane in greenhouse conditions - Paes, Bruno; Fabiano Braz Geraldo, Héctor; Gonçalves de Oliveira, Cláudio Marcelo; Marcondes de Almeida, José Eduardo (REVISTA DE AGRICULTURA, 2026)
Sugarcane is a major crop in Brazil, and its extended growth cycle favors the buildup of plant-parasitic nematodes such as Pratylenchus zeae and Meloidogyne javanica. This study evaluated the effects of different isolates of Metarhizium anisopliae and Purpureocillium lilacinum from the Biological Institute on nematode suppression and sugarcane performance. Two greenhouse experiments were conducted: Experiment I used naturally infested soil, and Experiment II used sterilized substrate inoculated with P. zeae. In Experiment I, isolates Pl06 and Ma04 reduced P. zeae by 59% and 66%, respectively, while Pl02 and Pl06 reduced M. javanica by 87% and 68%. In Experiment II, Ma04 reduced P. zeae by 74% (Rf = 2.5), and Pl06 by 64% (Rf = 3.5). Both isolates improved plant growth. These results show that Ma04 and Pl06 are promising agents for nematode management in sugarcane.